Case Report: Mycoplasma pneumoniae-induced rash and mucositis in a child - Mo, Xiaoying; Wang, Meihua; Jiang, Xue; Jin, Li (Frontiers in Medicine, 2025)
RationaleMycoplasma pneumoniae (MP) is a common pathogen responsible for pediatric community-acquired pneumonia. MP infection can also induce extrapulmonary manifestations, including mucocutaneous eruptions. Mycoplasma pneumoniae-induced rash and mucositis (MIRM) is a relatively newly described entity distinct from erythema multiforme (EM), Stevens-Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN). However, MIRM remains underrecognized, with limited cases reported in China.Patient concernsA previously healthy 10-year-old boy presented with fever, cough, severe mucositis (oral and ocular involvement), and disseminated rash for 5 days.DiagnosesThe patient was diagnosed with Mycoplasma pneumoniae-induced rash and mucositis (MIRM), confirmed by clinical presentation and laboratory detection of MP nucleic acid.InterventionsThe treatment regimen for the patient included intravenous azithromycin, methylprednisolone at a dosage of 1 mg/kg/day, intravenous immunoglobulin (IVIG), vitamin C, oral antihistamines, topical treatments for mucosal care, ophthalmic ointment, and calamine lotion. After 1 week, due to a persistent cough and a positive Mycoplasma pneumoniae (MP) nucleic acid test, the patient’s treatment was transitioned to oral doxycycline.OutcomesThe patient experienced significant clinical improvement after 14 days, with resolution of rash, mucosal lesions, and cough. Follow-up tests confirmed clearance of MP nucleic acid and normalization of inflammatory markers.LessonsMIRM is a distinct mucocutaneous entity associated with MP infection. Pediatricians should recognize its clinical presentation early to provide prompt targeted therapy and supportive care, thus preventing complications.